Water cut measurement of oil–water two-phase flow in the resonant cavity sensor based on analytical field solution method. (April 2021) - Yang, Yiguang; Xu, Ying; Yuan, Chao; Wang, Jinghan; Wu, Haitao; Zhang, Tao
Highlights: Analytical field solution method (AFSM) was introduced for water cut in oil-water flow. Boundary Field Factor (BFF) was proposed for correcting the AFSM. The method and model were validated in continuous flow with various flow patterns. Comparing with previous approaches, the model proposed has a better performance. Abstract: Microwave resonant cavity method has become one of the most attractive measurement ways in the petroleum industry. The exploration of measurement models is of great significance to the development of the technology. In this paper, we designed a fluid-passing microwave resonant cavity sensor (MRCS-FP) and established a novel prediction model of water cut in oil–water two-phase flow by introducing the analytical field solution method ( AFSM). The measurement accuracy is inevitably affected by the leakage of the electromagnetic field. Aiming at the above issue, boundary field factor (BFF), which was determined from the results of numerical simulation, was proposed to modify the prediction model. Finally, the experimental results of oil–water two-phase flow show that the prediction model with BFF performed better for water cut ranging from 30% to 100% and flow rate ranging from 3 to 7 m 3 /h. The relative error is better than ±5%, and 85% of the experimental points is less than ±3%.